Physical Fitness and Learning Achievement Academic in Children Aged 10-12 years - Pardilla, Herli (INSPIREE: Indonesian Sport Innovation Review, 2021)
The purpose of the study. The purpose of this study was to determine how big the impact of physical fitness on student achievement Materials and methods. The method in this research is a path analysis method with a correlational test technique. Correlational refers to taking the rsquare hypothesis, which is how big the impact of the correlation between physical fitness and student learning achievement is and this study uses the SPSS Version 25 application. Results.The results found that the level of the variable physical fitness on learning achievement with r = 0.708 with rsquare = 0.501 Coefficients sig value . 0.000. It turns out that the value of sig. 0.000 is less than the probability value of 0.00 or the value of 0.05>0.000. Conclusions.  Then Ha is accepted and H0 is rejected, meaning that the path analysis coefficient is significant. This study proves that there is a direct impact of physical fitness on student achievement.